A Process Model of Formative Work to Strengthen a Prison Health Surveillance System - Jessica Gaber; Njideka Sanya; Jennifer Lawson; Iridian M. Grenada; Fiona G. Kouyoumdjian (Frontiers Media S.A., 2024)
Worldwide, there is a lack of systematically collected health data on people who are incarcerated. Our objective in this paper was to describe a process model of formative work for a project to strengthen health surveillance for people incarcerated under a Canadian prison authority. We have developed project structures and processes, and we are evaluating project partnerships. To inform prison health surveillance foci, we are conducting a review of literature on best practices, a qualitative study to understand stakeholders' needs and priorities, and mapping work to understand available prison health-related data. Developing and implementing prison health surveillance is gradual and developmental, necessitating time to build relationships and obtain approvals. The needs and interests of knowledge users should be prioritized, but there may be challenges to achieving a coherent vision due to feasibility and differing needs and objectives of various stakeholders. Developing collaborative relationships could help bridge this gap.